2021
DOI: 10.1029/2020jb020807
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Geophysical Imaging of Weak Zones on Iliamna Volcano, Alaska: Implications for Slope Stability

Abstract: Water‐saturated, hydrothermally altered rocks reduce the strength of volcanic edifices and increase the potential for sector collapses and far‐traveled mass flows of unconsolidated debris. Iliamna Volcano is an andesitic stratovolcano located on the western side of the Cook Inlet, ∼225 km southwest of Anchorage and is a source of repeated avalanches. The widespread snow and ice cover on Iliamna Volcano make surface alteration difficult to identify. However, intense hydrothermal alteration significantly reduces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 82 publications
(159 reference statements)
1
6
0
Order By: Relevance
“…When modeling a homogeneous subsurface property distribution the most likely flank to collapse was estimated to be the north-western flank, however, when incorporating rock alterations mapped by the AEM data, the south-eastern flank was estimated to having a higher susceptibility to failure. Similar results where also obtained by Peterson et al (2021), which show that particularly deep hydro-thermal alteration of the Iliamna Volcano considerably increases the susceptibility of slope failure, but also increases the potential volume of material that could be released during failure (Fig. 18).…”
Section: Process-based Inversionsupporting
confidence: 85%
See 1 more Smart Citation
“…When modeling a homogeneous subsurface property distribution the most likely flank to collapse was estimated to be the north-western flank, however, when incorporating rock alterations mapped by the AEM data, the south-eastern flank was estimated to having a higher susceptibility to failure. Similar results where also obtained by Peterson et al (2021), which show that particularly deep hydro-thermal alteration of the Iliamna Volcano considerably increases the susceptibility of slope failure, but also increases the potential volume of material that could be released during failure (Fig. 18).…”
Section: Process-based Inversionsupporting
confidence: 85%
“…Yet, in contrast to vadose zone or groundwater studies, where many process-based inversion approaches have been developed and used, in the field of natural hazards this is only now starting to emerge. Some recent studies have combined subsurface structures identified from airborne EM data with hydro-geomechanical models to assess the stability of volcano flanks (Peterson et al, 2021;Finn et al, 2018). By incorporating subsurface features into the slope stability model, Finn et al (2018) could improve the hazards assessment for slope failure of Mt.…”
Section: Process-based Inversionmentioning
confidence: 99%
“…For example, using AEM data, subsurface properties in Alaska over an area of about 300 km 2 have been estimated (31). Within the last few years, AEM surveys are covering increasingly larger areas at regional basin scales, as large as 140,000 km 2 (32), and are moving from predominantly flat areas [e.g., (33,34)] to mountainous environments (35)(36)(37). There is an increased effort to use AEM data to construct hydrological models from local to regional scales (38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%
“…As the technology develops, AEM survey has been applied extensively in groundwater detection (Ball et al., 2020; Klee, 2013; Mikucki et al., 2015; Minsley et al., 2021; Thomsen et al., 2004; Viezzoli et al., 2010), mineral exploration (Koné et al., 2021; Okada, 2020; Roach et al., 2014), urban investigation (Steuer et al., 2020) and geological mapping (Dzikunoo et al., 2020; Jordan et al., 2009; Ley‐Cooper & Brodie, 2020; Rey et al., 2019; Silvestri et al., 2019; Wong et al., 2020). Recently, it has been exploited specifically in confined aquifer detection (Dugan et al., 2015), subglacial hydrology (Blatter et al., 2018), and volcano hazards (Dumont et al., 2019; Peterson et al., 2021).…”
Section: Introductionmentioning
confidence: 99%